2018
DOI: 10.1007/s11538-018-0445-z
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Dynamics of an SIS Model with Age Structure on Heterogeneous Networks

Abstract: Infection age is often an important factor in epidemic dynamics. In order to realistically analyze the spreading mechanism and dynamical behavior of epidemic diseases, in this paper, a generalized disease transmission model of SIS type with age-dependent infection and birth and death on a heterogeneous network is discussed. The model allows the infection and recovery rates to vary and depend on the age of infection, the time since an individual becomes infected. We address uniform persistence and find that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…In order to better describe the dynamics of disease, we will model the spread of disease in heterogeneous networks. Chen et al [3] took into account that not only could nodes be in states S and I, but also they belong to different connectivity classes k and built a mean-field equations which was degreedependent. They showed that basic reproduction number and the disease dynamics relied not only on the network structure, but also on an age-dependent factor.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better describe the dynamics of disease, we will model the spread of disease in heterogeneous networks. Chen et al [3] took into account that not only could nodes be in states S and I, but also they belong to different connectivity classes k and built a mean-field equations which was degreedependent. They showed that basic reproduction number and the disease dynamics relied not only on the network structure, but also on an age-dependent factor.…”
Section: Introductionmentioning
confidence: 99%
“…The explored nodes are added into the basic susceptible-infected-recovered (SIR) framework, and the immune loss area and death zone are inserted into the basic SIR framework to establish the susceptible-explored-infected-recovered-susceptible (SEIRS) model. References [ 12 , 13 ] introduced that the threshold property of the basic reproduction number was introduced for the propagation model of age-dependent SIS (susceptible-infection-susceptible) diseases in heterogeneous networks. The introduction of a popular threshold can accurately grasp the control effect of the network.…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al employed heterogeneous and stochastic agent-based models to analyze the characteristics of infectious diseases’ super spreaders [ 18 ]. Researchers also paid attention to epidemic dynamics in heterogeneous networks with different connectivities [ 19 , 20 , 21 ], and went forward and investigated epidemic spread in weighted networks representing the heterogeneity of individual interaction strengths [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%